'I Am Also Having Mother Once, and She Is Loving Me': Reading Cary Joji Fukunaga's Beasts of No Nation in a Post-Network Era. (28th December 2019) - Snell, Heather
Abstract: This article examines Cary Joji Fukunaga's film adaptation of Uzodinma Iweala's Beasts of No Nation, with a special focus on the final scene, in which a counsellor is assigned to help the protagonist deal with the trauma of having been a child soldier. While the casting of a black African actor as the counsellor in Fukunaga's film may appear to detract from the novel's interrogation of the uneven power relations between Africa and America, an interpretation oscillating between novel and film reveals that there may be some benefits to erasing the white saviour figure from the scene. The erasure of a white American character not only redirects the focus to relations among Africans but also comments indirectly on the circulation of transnational films via streaming services such as Netflix. Reading in between adapted text and adaptation also yields some important insights about Beasts ' critical engagement with the politics of circulation, reception, and consumption of child-soldier narratives at a time when such narratives have become popular among transnational audiences.